Lymphedema: another aspect in cutaneous leishmaniasis - Shamsuddin, Syed; Mohammad, Niaz; Asad, Faria; Nabi, Haroon; Ahmad, Syed Bilal (Journal of Pakistan Association of Dermatologists, 2016)
Background Cutaneous leishmaniasis (CL) is a common parasitic disease of the skin. Ugly scarring is a common sequel of CL. We report lymphedema, another disfiguring complication, in our patients in this chronic illness. Â Objective The main objective of this study was to determine the incidence of secondary lymphedema in leishmaniasis of lower legs and feet. Â Patients and methods This study was conducted at multiple centers in Balochistan province of Pakistan from 1st Feb, 2008 to 12th Sep, 2008. Out of 1920 patients with CL examined over this duration, 567 patients having the disease on the lower legs and feet were recruited in the study. All these patients were assessed for the presence of lymphedema of the involved limbs while edema observed was sorted into mild, moderate and severe categories. Follow up period was six weeks in order to observe the outcome of this complication. Â Results Out of the total number of 1920 patients, 567 (29.5%) had leishmaniasis of the lower legs and feet and out of these 157(27.7%) patients developed lymphedema of the affected limbs. Among these 157 patients, 76(48.4%) had mild edema, 52 (33.1%) had moderate edema and 29 (18.5%) had severe edema. Over a six weeks follow up period edema persisted in 43% of the patients inspite of successful treatment of CL with injectable antimony therapy. Â Conclusion Cutaneous leishmaniasis can lead to lymphedema of the lower legs and feet and has to be considered while enlisting the causes of secondary lymphedema.Â